Quality Seed Production Process According to Standards - Marsa; Satya Apriliansyah (Journal of Agro Complex Development Society, 2026)
Quality seed is a fundamental input in agricultural production, directly influencing crop yield, resilience, and uniformity across farming systems. However, many seed production systems in developing regions still rely on informal practices that do not fully comply with established seed quality standards, resulting in low genetic purity, high contamination, and variable germination performance. This study develops a conceptual framework for the Quality Seed Production Process According to Standards by synthesizing principles from international seed certification schemes, national regulations, and best practices in field and post harvest management. The framework integrates four key layers genetic and varietal integrity, field production and isolation, post harvest handling and quality testing, and certification and traceability to illustrate how seed producers can systematically meet physical, physiological, and genetic quality requirements. The findings highlight that adherence to seed production standards can increase productivity, reduce the risk of seed-borne diseases, and improve farmers’ confidence in formal seed systems, while policy implications include strengthening certification institutions, promoting producer training, and developing digital traceability tools for seed lot monitoring.